Understanding by Older Patients of Dialysis and Conservative Management for Chronic Kidney Failure - Tonkin-Crine, Sarah (Am J Kidney Dis, 2015)
BACKGROUND: Older adults with chronic kidney disease stage 5 may be offered a choice between dialysis and conservative management. Few studies have explored patients’ reasons for choosing conservative management and none have compared the views of those who have chosen different treatments across renal units. STUDY DESIGN: Qualitative study with semistructured interviews. SETTINGS & PARTICIPANTS: Patients 75 years or older recruited from 9 renal units. Units were chosen to reflect variation in the scale of delivery of conservative management. METHODOLOGY: Semistructured interviews audiorecorded and transcribed verbatim. ANALYTICAL APPROACH: Data were analyzed using thematic analysis. RESULTS: 42 interviews were completed, 4 to 6 per renal unit. Patients were sampled from those receiving dialysis, those preparing for dialysis, and those choosing conservative management. 14 patients in each group were interviewed. Patients who had chosen different treatments held varying beliefs about what dialysis could offer. The information that patients reported receiving from clinical staff differed between units. Patients from units with a more established conservative management pathway were more aware of conservative management, less often believed that dialysis would guarantee longevity, and more often had discussed the future with staff. Some patients receiving conservative management reported that they would have dialysis if they became unwell in the future, indicating the conditional nature of their decision. LIMITATIONS: Recruitment of older adults with frailty and comorbid conditions was difficult and therefore transferability of findings to this population is limited. CONCLUSIONS: Older adults with chronic kidney disease stage 5 who have chosen different treatment options have contrasting beliefs about the likely outcomes of dialysis for those who are influenced by information provided by renal units. Supporting renal staff in discussing conservative management as a valid alternative to dialysis for a subset of patients will aid informed decision making. There is a need for better evidence about conservative management to support shared decision making for older people with chronic kidney failure.